Pengembangan Sistem Pemantauan Cryptocurrency Berbasis Web Menggunakan Metode Waterfall - Teti Desyani; Aries Saifudin; Hanaan Ridho Altamerano; Sugeng Gunantio; Syahrul Al-Rasyid; Yudha Eka Saputra (Jurnal Informatika Universitas Pamulang, 2022)
The rapid development in trading activities in the digital era as it is now has made large-scale business actors and individuals follow suit. Various trading activities that were done manually can now be done automatically with the help of various developers who are assisted by an internet connection. So we developed a website-based application to monitor the price of each crypto currency. In this website application we prioritize fast and real monitoring for each crypto coin. That way, trading business people or traders can monitor the prices of crypto coins in real and accurate terms. The purpose of this application is to enable users to monitor or see real-time bitcoin values in Indonesia. The SDLC technique is used to develop and alter systems, and it is grouped into stages such as system planning, system analysis, system design, system implementation, system testing, and system maintenance. This Application Design acts as a container for individual investors to follow the value of cryptocurrencies.